Development Of Tourism Culture Of Students Using Modern Methods By Means Of Digital Technologies - Amanbaev Timur Gayratbaevich (Zien Journals, 2025)
This article explores the use of modern digital technologies to develop the tourism culture of students. It highlights methods such as virtual tours, interactive learning, and multimedia platforms as effective tools for enhancing the educational process. The study emphasizes how digital tools facilitate the acquisition of cultural knowledge, cognitive skills, and students’ interest in tourism.
Keywords: tourism culture; digital technologies; students; virtual tours